Mengembangkan Perkembangan Sosial Emosional Anak Usia 4-5 Tahun Melalui Alat Permainan Edukatif Dari Kardus Bekas - Khotimul Fitria; Fitrianti Wulandari (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This study uses a descriptive survey method. With the use of this "cardboard" used item to be used as an Educational Game Tool (APE), besides that, another benefit is being able to develop the social emotional aspects of children when the toys are given and of course have a further impact on increasing the direct learning experience that children get, as well as increasing interest. study. Therefore, the researcher wants to know more about the development of children's creativity through used goods which are used as a source of children's learning to stimulate the experience and development of children's creativity through educational game tools from used goods.